Combining visual and textual data for assessing destination image: Lake tourism example. Issue 4 (2nd October 2017) - Rodrigues, Ana Isabel; Correia, Antónia; Kozak, Metin
Abstract: Lake-destination areas are highly favoured places for tourists due to their aquatic environment as well as areas' rich surrounding regions. Existing literature on marketing lake-destination marketing lacks insights to identify the main image attributes driving visitors and understanding the lake tourism concept. The present study examines textual and pictorial data to generate image variables about Alqueva Lake, Portugal, the largest manmade lake in Europe. Results provide insights to characterize the potential of lake-destinations and to develop a final list of variables specifically related to this destination type. The aim is also to help those involved in marketing the Alqueva Lake as a destination to identify and propose an adequate strategy.